Avaliação radiológica da motilidade gástrica de ratos wistar, submetidos a ação da eletroacupuntura e de extratos de Rosmarinus officinalis - Carnevali, Taiane Rita (2012)
The treatment of gastrointestinal disorders using natural methods such as electroacupuncture and phytotherapy, has been deployed worldwide in human and veterinary medicine. Thus, the work was to determine the action of electroacupuncture and the aqueous and ethanol extracts of Rosmarinus officinalis on gastric motility of rats assessed by radiographic examination, in addition to reporting a case of Situs Inversus Totalis in a Wistar albino rat, diagnosed during the experiment. For evaluation of electroacupuncture on gastric motility, we used 24 Wistar rats, divided into four treatments, T1: electroacupuncture point E36 and BP6; T2: electroacupuncture in falses stitches; T3: sterile distilled water and T4: metoclopramide. Five metallic spheres were administered per animal and performed serial radiographs to monitor the gastric emptying time in the different treatments. By analyzing the time of exit the first spheres, the animals of group T1 ha d an average of 3,5h; in T2 the average was greater than 6h; T3 was 5,3h and the T4 observed average of 4,6h. the action of electroacupuncture was comparable to the action of metoclopramide, which is know to increase peristalsis, whereas the response of the Shan group (T2) was close to the negative control group. In the determination of gastric motility with the use of aqueous and ethanol extracts of R. officinalis, were used 48 albino rats, divided into eight groups, group TE1: ethanolic extract 125mg/kg; group TE2: ethanolic extract 250mg/kg; group TE3: ethanolic extract 500mg/kg; group TA1: aqueous extract 125mg/kg; group TA2: aqueous extract 250mg/kg; group TA3: aqueous extract 125mg/kg; group T4: metoclopramide, and group T5: sterile distilled water. After the treatments were administered five metallic spheres per animal and performed serial radiographs, each hour, to monitor the gastric emptying time. By analyzing the amount of spheres that left the stomach of experimental animals up to 3h, it was observed that there was no difference in treatment, as to the number of spheres removed. Were eliminated 76,6% in TE1, in TE2 60% (n=18), in group TE3 63,3% (n=19), in TA1 (n=14) 46,6%, in group TA2 50% (n=15) and, finally, the group TA3 86,6% (n=26) while in the control groups (T4) was 100% (n=30) and T5 93,3% (n=28). During the study, was diagnosed by radiographic examination, a rare case of Situs Inversus Totalis in albino rat, showing all the organs of the opposite side to its physiological position. Thus, it is concluded that electroacupuncture at points BP6 and E36, showed a significant increase of gastric peristalsis, reducing emptying time. In addition, the aqueous and ethanolic extracts of R. officinalis decrease gastric motility in rats. Suggesting that these may be useful in disorders of motility, however further studies should be conducted in order to better determine this action. The report of Situs Inversus Totalis draws attention to the importance of this type of diagnosis in order to remove the animal from the reproduction, as there are not sufficient studies to determine the reflection of the health condition of animals.